The nearest results of the treatment of exacerbated course of generalized periodontitis in patients with a predominance of the parasympathetic nervous system - Батіг, Віктор Маркіянович (Actual Dentistry, 2019)
Objectives. The exacerbated course of generalized periodontitis has certain features of clinical course and, accordingly, complex treatment. In the emergence of an exacerbated course of periodontal disease, the general condition of the patient’s organism is of particular importance. Taking this into account, a medicamental treatment scheme for the exacerbated course of generalized periodontitis in patients with a predominant parasym pathetic autonomic nervous system was proposed. Aim. The determination of the nearest results of clinical efficacy of the proposed complex treatment of patients with exacerbated course of generalized periodontitis in the presence of parasympathetic nervous system predominance. Materials and methods. Clinical investigation was conducted on groups of 60 patients with exacerbated course of generalized periodontitis and prevalence of the parasympathetic nervous system. Medicamental treatment of 40 patients was performed using proposed sedation composition. Patients were conducted a comprehensive examination of periodontal tissue before treatment and after treatment. To evaluate the clinical efficacy of treatment used Schiller-Pisarev test (1962), the index of PMA by C. Parma (1961), hygienic index OHI-S (1964), the vacuum test by Kulazhenko (1961). Results. As a result of the investigation it was found that the usage of the proposed sedation composition in the complex therapy of patients with exacerbated course of generalized periodontitis can effectively inhibit the dystrophic inflammatory process in periodontal tissues. This confirms by the decline in the index PMA, increase the time of formation of hematoma during the vacuum tests on Kulazhenko, improving oral hygiene. Conclusions. Usage of the proposed sedation composition increases the effectiveness of treatment of exacerbated course of generalized periodontitis in patients with predominance of the parasympathetic nervous system. Key words: exacerbated course of generalized periodontitis, patients with predominance of the parasympathetic nervous system, sedation composition.